PENERAPAN UI/UX DENGAN METODE DESIGN THINKING PADA SINBAR (SISTEM INFORMASI INVENTARIS BARANG KANTOR) PT DAYAMITRA TELEKOMUNIKASI, TBKREGIONAL SUMBAGSEL - Devi Wulan Safitri; Evi Fadilah (Jurnal Riset Sistem Informasi, 2024)
This research on the UI/UX Design of the Inventory Information System uses the Design Thinking method. The goal is to understand the needs of users, namely admins and employees, produce intuitive solutions by creating an easy-to-use interface, increase user satisfaction and comfort, and minimize the risk of errors in design by utilizing the Figma tool. The use of tools is expected to provide convenience in the layout of the interface and user experience (UI/UX) that is in accordance with user expectations. The conclusion of this study is a computerized Web-Based Office Inventory Information System application to assist users in the process of creating available Office Inventories and incoming/outgoing goods, searching and monitoring and creating reports on goods data in PT Dayamitra Telekomunikasi.